NÉMET–OSZTRÁK–MAGYAR SZAKÉRTŐI BIZOTTSÁGI KONFERENCIA A LENGYEL VÁMPOLITIKA KÉRDÉSÉRŐL (1916. AUGUSZTUS 29 – SZEPTEMBER 1.): GERMAN–AUSTRO–HUNGARIAN CONFERENCE OF SPECIALIST-COMISSSION IN THE ISSUE OF THE CUSTOMS POLICY (29. AUGUST – 1. SEPTEMBER 1916) - Tefner, Zoltán (Közép-Európai Közlemények, 2020)
In my paper I present the discussion between the German Empire and the Austro–Hungarian Monarchy how must be develop the economical system in the Polish Kingdom after the war finished victorious against the entente-mights. The Central Powers had occupied in August 1915 the full teritory of the earlier so-callied Russain-Poland and the sherad the country in two parts, a German and an Austro-Hungarian territory, arranged there two General-Military-Gouvernements: the German part with the capitol of Warsaw and an Autrichian zone with the centre in Lublin. The two great powers had rival in the polish issue during of each of the four war-years. At the high sommer of 1916 – because of the catastrophal defeat against the Russian army – Germany had taken lead over the Danube Monarchy in this rivalisation. As the more powerful partner he vindicated for him self the right to say in the matter: what kind of the custom-system must they arranged in Poland. The Germans wanted Poland to draw into the German custums system. The representant and leader of the Austro-Hungarian delegation, Kajetán Mérey upholded the case of the independent Polish custems system. The conference could finish the discusson without result.